CULTIVATING CREATIVITY: THE EMERGENCE OF ART SCHOOLS IN INDIA - Upadhyaya, Alpana; Wadhwa, Vinny (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Education stands as a cornerstone in the advancement of any nation, serving as a catalyst for progress and enlightenment. It acts as a key, unlocking doors of opportunity and enriching the intellect of individuals. Concurrently, art, a timeless facet of human civilization, bears witness to the unique essence of every society throughout history. However, education not only fosters the appreciation of art but also cultivates a liberated and conscientious mindset. Thus, education in the arts emerges as a conscious endeavor, wherein individuals strive to transform and elevate their lives. The inception of art schools in India finds its roots in the colonial era, particularly under British rule, where the modern education system took shape. Consequently, the establishment of formal institutions for artistic education in the country can be attributed to this pivotal historical period.